SPECIAL ASPECTS OF FINANCIAL INSTRUMENTS VALUATION FOR TRAINING SPECIALISTS OF ECONOMIC MAJORS - Masko, Ludmila; Pankou, Pavel (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Nowadays financial instruments market is the high-priority area of economic development in Belarus, where important place is given to creation the variety of corporate financial instruments, which requires prompt response from economic sciences.However, fundamentals of financial instruments valuation and ways of reflecting them in financial statements are complex issues that require special approach in the process of instruction economic disciplines, related to these topics. Therefore, the purpose of this study is to form systematic understanding the basics of financial instruments valuation based on the study their economic essence and the development of practical guidelines for valuation methods application. In the study have been proposed new, different from existing, questions that should be considered in the course structure when studying financial instruments by students of economic majors; have been offered practical guidelines on the ways of financial instruments valuation in the form of applied models that contribute to further understanding their economic essence, creating essentials for effective usage these instruments in future. In the study the following scientific methods were used: analysis, synthesis, generalization, induction, deduction, observation, formalization. The research is based on the provisions of IFRS, works of domestic and foreign economists, current Belarussian legislation on the considered issue.